2015
DOI: 10.4236/ijcm.2015.61006
|View full text |Cite
|
Sign up to set email alerts
|

Scald Burns in Children. An Analysis with Special Attention to the Roma Ethnic Group in East Slovakia

Abstract: Objectives: A retrospective analysis of scald burns in children in a region with a significant prevalence of Roma ethnicity living in poor socioeconomic situation. Patients: During 3 year period 273 children were admitted to the Clinic of Burns and Reconstructive Surgery of our hospital; 201 of them were with scald burns accounting for 73.6% of all pediatric burn admissions. More than half (58.7%) of the 201 children with scald burns were of Roma ethnicity. Results: The average BSAB of the children with scald … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
1
0
4
Order By: Relevance
“…Most of the above-discussed patterns of health-endangering exposures faced by Roma have been relatively well studied for Slovakia. Rigorous scientific studies have found the segregated Roma in Slovakia to live in unhealthier material circumstances (Frisman et al 2015;Majdan et al 2012;Škobla et al 2016) (for an illustration, see Figure 1.6), to smoke and use illicit drugs more frequently (Babinska et al 2013;e.g. de Courten et al 2003;Hubková et al 2018;Vazan et al 2011), to eat an unhealthier diet and be more obese (Hijova et al 2014;Krajcovicova-Kudlackova et al 2004;Petrásová et al 2014) and to engage in less healthy physical activities and incur more injuries Babinska et al 2013;Kolarcik et al 2010).…”
Section: Pathways In Slovakiamentioning
confidence: 99%
“…Most of the above-discussed patterns of health-endangering exposures faced by Roma have been relatively well studied for Slovakia. Rigorous scientific studies have found the segregated Roma in Slovakia to live in unhealthier material circumstances (Frisman et al 2015;Majdan et al 2012;Škobla et al 2016) (for an illustration, see Figure 1.6), to smoke and use illicit drugs more frequently (Babinska et al 2013;e.g. de Courten et al 2003;Hubková et al 2018;Vazan et al 2011), to eat an unhealthier diet and be more obese (Hijova et al 2014;Krajcovicova-Kudlackova et al 2004;Petrásová et al 2014) and to engage in less healthy physical activities and incur more injuries Babinska et al 2013;Kolarcik et al 2010).…”
Section: Pathways In Slovakiamentioning
confidence: 99%
“…Получените резултати сочат, че най-голям процент от термичните травми са в следствие попарване -66.3%. Подобни са данните, отчетени и при проучване в Словакия, където то е 73.6%, 26.4% е пламъково изгаряне и значително по-малък процент са останалите [10,12,14,26,30]. Такива са стойностите и при други изследвания, като процентът на попарванията варира от 45 до 88 от всички изгаряния [2,4,5,9,10,15,16,21,22,24,[26][27][28][29]31].…”
Section: обсъжданеunclassified
“…При повече от половината случаи с попарване причинител е гореща вода [2,3,21], а в 48% -друга гореща течност -чай, кафе, мляко, супа, мазнина и др. Това кореспондира с резултатите от други проучвания [12,21]. P. Agbenorku отчита дори по-голям процент въздействие на гореща вода -68.1% към 32.9% от други течности [2,14].…”
Section: обсъжданеunclassified
See 2 more Smart Citations